UJI KEANDALAN PROTOTYPE TURBIN ANGIN SAVONIUS TIPE-U SEBAGAI PEMBANGKIT LISTRIK ALTERNATIF - Siregar, Ahmad Marabdi; Lubis, Faisal (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2019)
This time and in the future we must utilize renewable energy sources. The energy we use today is still dominated by fossil fuels which will gradually run out. One of the environmentally friendly renewable energy sources that we can use is wind energy. Wind turbines can be used to produce electrical energy, so that it can overcome one of the energy problems for people in need. Wind turbines that are suitable for low wind speed and medium wind speed are Savonius turbine types. For the development of the research a wind turbine prototype was made. This test was carried out on the prototype type U-type savonius wind turbine and the aluminum-based blade. The rotor has a diameter of 350 mm and a height of 440 mm. The study parameters measured are wind speed, rotor rotation speed, voltage and current of the generator. The performance of the U-type savonius wind turbine in this test is at wind speeds of 4 m/s to wind speeds of 6 m / s. At 6 m / s wind speed the maximum rotation of the turbine shaft is 33.80 rpm, wind power is 18.65 watts and produces electric power of 5.24 watts.